The contributions and benefits of hippotherapy as a speech therapy method: a literature review (Research, Society and Development, 2021)
Hippotherapy can be understood as a therapeutic and educational method that uses the horse within an interdisciplinary approach, in the areas of health, education and riding, seeking the biopsychosocial development of individuals who have some type of disability or special needs, through the employment of the horse as a true promoter of physical, psychological and educational gains. The aim of this research is to analyze the forms of speech therapy intervention in hippotherapy. Regarding the methodology, the research can be understood as a literature review through the analysis of several research sources, highlighting scientific articles available in the databases of SCIELO, CAPES and PUBMED. Through this research it was concluded that the role of the speech therapist within the hippotherapy team, in addition to acting directly with the practitioner, participates in the therapeutic planning, clarifying, demonstrating and proving the importance of speech therapy work for the team, guiding the practitioner's family . however, it was found that there are no procedures and a broad, uniform theoretical foundation for speech therapy practice in hippotherapy.